Local Wisdom Sebagai Penguat Implementasi Good University Governance Perguruan Tinggi Swasta di Kabupaten Jayawijaya - Nur Aini; Akbar Silo; Untung Muhdiarta; Hiskia C.M. Sapioper; Vestus Febrian Aristoteles Jawan (Program Doktor Ilmu Sosial Universitas Cenderawasih, 2026)
The main problem of this research is the low quality of student services in private universities in Jayawijaya Regency due to the suboptimal implementation of good university governance. This study aims to analyze the implementation of governance, identify inhibiting factors, and explore the role of local wisdom in strengthening governance. The method used is descriptive qualitative with data collection through in-depth interviews, observation, and documentation. Research participants included leaders, staff, lecturers, students, and alumni. Data analysis used the Miles and Huberman model with source triangulation for validity. The results of the study indicate that the integration of local wisdom significantly increases transparency, accountability, and stakeholder participation, strengthens governance implementation, and improves the quality of student services, becoming a relevant adaptive strategy for universities in the 3T region.